La potencialidad didáctica del Word Repetition Game: ejemplo de una interacción entre estudiante y profesor - Torresan, Paolo (Huarte de San Juan. Filología y Didáctica de la Lengua, 2012)
This essay describes an impro task that can be adapted to the language classroom: the Word Repetition Game (Meisner, Longwell 1987). This task involves two participants sitting opposite each other who make observations in the present tense about the other’s current state (posture, clothing etc.). They may also formulate statements not based in reality. It is then the other participant’s turn to continue the conversation with new statements: he/she may simply repeat what the partner has said (changing the subject as appropriate), or may modify the nature of the statement, changing it to a question or negation, with appropriate modification to the intonation. The first speaker/sender may then, in turn, repeat the same statement(s) or, should he/she wish, formulate a new one/new ones. This article features a transcript of a conversation held between a Polish student and a teacher in an Italian FL classroom, with the corresponding translation into Spanish. We then highlight certain passages that are significant in terms of language teaching.